2023
DOI: 10.1101/2023.12.13.571574
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feature attention graph neural network for estimating brain age and identifying important neural connections in mouse models of genetic risk for Alzheimer’s disease

Hae Sol Moon,
Ali Mahzarnia,
Jacques Stout
et al.

Abstract: Alzheimer’s disease (AD) remains one of the most extensively researched neurodegenerative disorders due to its widespread prevalence and complex risk factors. Age is a crucial risk factor for AD, which can be estimated by the disparity between physiological age and estimated brain age. To model AD risk more effectively, integrating biological, genetic, and cognitive markers is essential. Here, we utilized mouse models expressing the major APOE human alleles and human nitric oxide synthase 2 to replicate geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
(127 reference statements)
0
0
0
Order By: Relevance
“…AD is a multifactorial disease that could be characterized by various cellular and molecular processes; although the actual cause of this disease remains unknown, age is believed to be the highest risk factor [ [2] , [3] , [4] , [5] , [6] , [7] ]. Studies have shown a significant correlation between aging and numerous AD pathogenesis [ [10] , [11] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…AD is a multifactorial disease that could be characterized by various cellular and molecular processes; although the actual cause of this disease remains unknown, age is believed to be the highest risk factor [ [2] , [3] , [4] , [5] , [6] , [7] ]. Studies have shown a significant correlation between aging and numerous AD pathogenesis [ [10] , [11] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%